Robots and manufacturing automation - Asfahl, C. Ray, 1938- (New York : Wiley, 1992)
Robots and Manufacturing Automation Second Edition C. Ray Asfahl University of Arkansas 55391 3, 512 pp., cloth, 1992 A Complete Guide to Using Automation to Boost Productivity This applications-oriented book surveys the wide spectrum of automated systems available to increase manufacturing productivity. It covers all aspects of automation including robots, numerical control machines, programmable controllers, computer controllers, and microprocessor-based automated systems. Technical topics are explained in an easy-to-understand style and illustrated with vivid images. Every chapter includes quantitative exercises or problems and design case studies to help solidify understanding of the material. The new Second Edition is now completely current in coverage, and includes a number of enhancements: Text expansion (approximately 20 per cent) ensures complete coverage of the field. Careful changes have modernized the text and emphasize the most recent and widely-used automation equipment and techniques. Updated coverage now includes concepts which show how to design products to enhance automation and manual production. New chapters on Machine Vision and Computer Integrated Manufacturing (CIM) bring topic coverage to the cutting edge. The Robot Programming chapter contains new material on the AML Language.
This is a survey of the automated systems currently available for the improvement of manufacturing productivity. It features material on robots, numerical control machines, programmable controllers, computer controllers and microprocessor-based automation.
Getting Ready to Automate. Building Blocks of Automation. Mechanization of Parts Handling. Automatic Production and Assembly. Numerical Control and CAD/CAM. Industrial Robots. Teaching Robots to Do Work. Machine Vision Systems. Robot Implementation. Industrial Applications of Robots. Industrial Logic Control Systems. Logic Diagramming. Programmable Logic Controllers. On-Line Computer Control. Microprocessors. Computer Integrated Manufacturing. Ethics. References. Appendices. Index.
Includes bibliographical references (pages 460-466) and index.
Keywords: Robots, Industrial